Moderate Inflation : The Experience of Transition Economies: The Experience of Transition Economies - Cottarelli, Carlo (International Monetary Fund, 1998)
Many countries, including several transition economies, have in the last few years recorded a sharp decline in inflation, but have been unable to bring inflation down to lower single digits or to achieve price stability. In these countries, inflation has stabilized at moderate levels, with further progress becoming seemingly more difficult. What are the problems created by moderate inflation? What is the appropriate speed of disinflation? These and other issues related to disinflation in transition economies are taken up in this book, edited by Carlo Cottarelli and Gyorgy Szapary.